2021
DOI: 10.7759/cureus.14866
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Lung Ultrasound to Detect Pleural Adhesions: A Systematic Review and Meta-Analysis

Abstract: The usage of lung ultrasound as a preoperative examination for thoracic surgeries remains controversial. Our systematic review and meta-analysis aimed to evaluate preoperative lung ultrasound diagnostic accuracy for detecting pleural adhesions. We searched articles published in MEDLINE, Embase, CENTRAL, and the International Clinical Trials Registry Platform until October 2020. Inclusion criteria were observational studies, case-control studies, and case series assessing preoperative lung ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…On the other hand, the utility of preoperative lung ultrasound is also reported useful to detect pleural adhesions (24)(25)(26). A systematic review by Shiroshita et al showed very good results with the sensitivity of 70% and the specificity of 96% using ultrasound (24). Sasaki et al reported the negative predictive value of 87.7% and the positive predictive value of 50.0% (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the utility of preoperative lung ultrasound is also reported useful to detect pleural adhesions (24)(25)(26). A systematic review by Shiroshita et al showed very good results with the sensitivity of 70% and the specificity of 96% using ultrasound (24). Sasaki et al reported the negative predictive value of 87.7% and the positive predictive value of 50.0% (25).…”
Section: Discussionmentioning
confidence: 99%
“…We determined DCR to have a high specificity and negative predictive value, and the results of the examination was equal to or better than that of dynamic CT or dynamic MRI ( 19 , 20 ). On the other hand, the utility of preoperative lung ultrasound is also reported useful to detect pleural adhesions ( 24 - 26 ). A systematic review by Shiroshita et al showed very good results with the sensitivity of 70% and the specificity of 96% using ultrasound ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The options available for accurately diagnosing pleural adhesions are limited. To date, transthoracic ultrasound (US) ( 3 ), respiratory dynamic computed tomography (CT) ( 4 - 6 ), and dynamic cine magnetic resonance imaging (MRI) ( 7 - 9 ) have been proposed as diagnostic methods for pleural adhesions. However, these imaging modalities have constraints that make their universal application in preoperative testing impractical.…”
mentioning
confidence: 99%